2023
DOI: 10.3389/fsurg.2022.964044
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase (PLK) 5, a new member of the PLK family, serves as a biomarker to indicate anabatic tumor burden and poor prognosis for resectable non-small cell lung cancer

Abstract: ObjectiveA review argues that polo-like kinase 5 (PLK5) may be linked to unfavorable prognosis in non-small cell lung cancer (NSCLC) patients, which contradicts the discoveries from The Human Protein Atlas database (derived from TCGA analysis). This study intended to comprehensively confirm the association of PLK5 with clinical characteristics and prognosis in NSCLC patients.MethodsThis two-center, retrospective, cohort study enrolled 210 NSCLC patients receiving surgical resection. PLK5 protein and mRNA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…In view of earlier published studies supporting a tumor suppressor role of PLK5 expression in non-small-cell lung cancer [16,17], breast cancer [18], medulloblastoma [19] and glioblastomas [13], we were interested in expanding the available knowledge on the role of this kinase in additional cancer types. Our observation of high PLK5 expression in certain specific normal tissues led us to further investigate the expression profile of PLK5 in cancers of these same tissue types to determine its potential tumor suppressor role in these tissues.…”
Section: Plk5 Expression Is Downregulated In Cancer Tissues As Shown ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of earlier published studies supporting a tumor suppressor role of PLK5 expression in non-small-cell lung cancer [16,17], breast cancer [18], medulloblastoma [19] and glioblastomas [13], we were interested in expanding the available knowledge on the role of this kinase in additional cancer types. Our observation of high PLK5 expression in certain specific normal tissues led us to further investigate the expression profile of PLK5 in cancers of these same tissue types to determine its potential tumor suppressor role in these tissues.…”
Section: Plk5 Expression Is Downregulated In Cancer Tissues As Shown ...mentioning
confidence: 99%
“…Nevertheless, the role PLK5 plays in different cells and tissues remains vastly unknown, despite its identification over two decades ago. To date, very limited research has been performed regarding the role of PLK5 in cancer, with only a few studies showing decreased PLK5 expression in non-small-cell lung cancer [16,17], breast cancer [18], medulloblastoma [19] and glioblastomas [13]. Additionally, a 2016 study found a novel metastasis-associated three-nucleotide deletion mutation of PLK5 in clear cell renal cell carcinoma [20] and a 2020 study identified a rare p.G223V variant of PLK5 in a small subset of ovarian cancer patients [21].…”
Section: Introductionmentioning
confidence: 99%